Analisis Isi Konten Media Sosial Instagram Pemerintah Indonesia di Tingkat Kementerian dan Lembaga - Dimas Aditya Nugraha; Tito Edy Priandono; Nafira Fathin Ainiyyah; Yusuf Ilham (Jurnal Ilmiah Manajemen Informasi dan Komunikasi, 2024)
Government institutions need social media channels as a public communication tool to disseminate policies, programs and public information. The government needs to use social media channels to reach a wider community amidst the low level of public trust in government communications and information channels. The aim of the research is to analyze the substance of the content, namely the type and nature of the content, what the audience needs and what the content message needs to communicate to the audience. This research also seeks the content structure related to how content is prioritized, arranged, formatted and displayed in the media. The objects analyzed are Instagram social media in 100 ministries and agencies. This research uses a descriptive quantitative approach that focuses on analyzing the use of Instagram social media by ministries and government agencies in Indonesia. This method aims to provide a comprehensive picture of government digital activities and to analyze the effectiveness of the substance and structure of the content implemented. Instagram was chosen as the main focus because it is the social media platform most widely used by ministries/agencies. The research results show that each agency has various needs with different strategies for using Instagram social media. The ministry has optimized Instagram social media more than the government agencies. Interestingly, the agency produces more content than the ministry, but it is still not optimal. Meanwhile, on average, ministerial agencies still prioritize personal figures and institutional agencies prioritize public information, although they also still predominantly prioritize leadership elements. The results of this research suggest that the government, especially the Ministry of Communication and Informatics, can create standards in managing social media, especially in producing the structure and substance of content so that it can more optimally convey information and interact with the audience.